Global incidence, mortality and temporal trends of cancer in children: A joinpoint regression analysis. (13th July 2022) - Huang, Junjie; Chan, Sze Chai; Ngai, Chun Ho; Lok, Veeleah; Zhang, Lin; Lucero‐Prisno, Don Eliseo; Xu, Wanghong; Zheng, Zhi‐Jie; Elcarte, Edmar; Withers, Mellissa; Wong, Martin C. S.; ,
Abstract: Background/Methods: The Cancer Incidence in Five Continents Time Trends, Nordic Cancer Registries, Surveillance, Epidemiology and End Results, WHO Mortality databases were assessed to extract the Age‐Standardised Rates (ASR) of cancer incidence and mortality among children aged 0–14 years old. By using the ASRs, the country‐specific Average Annual Percentage Change (AAPC) and its corresponding 95% confidence interval (CI) were calculated to determine the epidemiological cancer trend. Results: In 2020, the highest incidence of childhood cancer was found in countries with higher Human Development Index (HDI) (ASR = 15.7), yet the highest mortality was found in countries with lower HDIs (ASR = 4.8). As for incidence, seven countries had positive AAPC among boys; Slovakia (AAPC2001–2010  = 4.98, 95% CI [1.66–8.40]), Ecuador (AAPC2003–2012  = 4.07, 95% CI [0.67–7.59]) and Thailand (AAPC2003–2012  = 3.69, 95% CI [0.37–7.11]) had the highest AAPC. Among girls, three countries had positive AAPC, which included Belarus (AAPC2003–2012  = 3.18, 95% CI [1.11, 5.29]), Canada (AAPC2003–2012  = 2.83, 95% CI [1.60, 4.07]) and Korea (AAPC2003–2012  = 1.76, 95% CI [0.23–3.32]). There was an overall decreasing trend of mortality. However, increased mortality was observed in two countries: Ecuador for boys (AAPC2007–2016  = 1.72, 95% CI [0.27–3.19]) and Austria for girls (AAPC2008–2017  = 4.11, 95% CI [0.38–7.98]). Conclusions: The largest mortality and mortality to incidence ratio of childhood cancer were found in low‐income countries. There was a substantial increasing trend of childhood cancer incidence, while overall its mortality has been decreasing over the past decade. More studies are needed to confirm the drivers behind these epidemiologic trends. Abstract : This study aimed to explore the most up‐to‐date global burden and incidence/mortality temporal trends of cancer among children. It was found that the largest mortality and mortality to incidence ratio of childhood cancer were observed in low‐income countries; a substantial increasing trend in childhood cancer incidence was found, but its mortality has been decreasing generally over the past decade.